Economic Sanctions against Russia: Assessing the Policies to Overcome their Impact - Belozyorov, Sergey A.; Sokolovska, Olena (Economy of Regions, 2020)
Starting from 2014 the European Union countries, the United States of America and some other states imposed economic sanctions against Russia, resulting in diversification of trade ties away from western partners (“pivot to the East” strategy). The mixed findings of recent sanctions literature related to their effectiveness and measures to overcome the negative consequences, has necessitated the examination of these issues for the case of anti-Russian economic sanctions. We use various macroeconomic data along with indicators of digital development and financial inclusion. The methodology comprises a combination of graphical, comparative, and correlation analysis. The analysis of external sector data shows that economic sanctions had substantial negative impact on trade and foreign direct investment with main senders. At the same time, the “pivot to the East” after 2014 has not been implemented yet as much as expected. To overcome negative impact of sanctions and to promote economic growth, the current diversification of ties should be accompanied by other measures, centred on digital development, digital financial technologies, and financial inclusion. We assess linkages between digital development and wealth inequality and we found that in most countries with moderate wealth inequality, including Russia, the digital transformation could bring more benefits in terms of economic growth, than in countries with lower wealth inequality. The overall study allowed us to examine digital policy implications to overcome the negative effects of sanctions in Russia. The obtained results will contribute to addressing the problem of optimisation of Russia’s behaviour as a target country that is the subject of future research.